Knowledge about composite restorations repair vs replacement- a survey among a subpopulation of saudi dental students - Alqarni, Mohammed; Khalil, Shamsun Nahar; Obied, Eman Saeed Saeed; Alshehri, Maha M; Assiri, Manar Ali Abdulgader; Mualwi, Sara Abdullah Muhammed; Thabet, Sultanah Mohammed Saeed; Khateeb, Shafait Ullah (Brazilian Dental Science, 2020)
Objectives: the purpose of this study was to evaluate the knowledge among dental students at King Khalid University, Jazan University, and Najran University in the kingdom of Saudi Arabia about when to repair or replace defective direct composite restoration. Materials and Methods: A questionnaire-based survey was formulated, pursuing the information about management (repair/replacement) of defective composite restorations and distributed among 200 dental students of three universities in the southern region of the kingdom of Saudi Arabia.The data were collected with the help of an online questionnaire. Data entry and the analysis were done using the statistical software package SPSS version 20.0. It was presented using descriptive statistics in the form of frequencies and percentages for qualitative variables, and range means and standard deviations for age, quantitative variable. Analytic statistics ere done using Chi-Square tests (x2) to test the significant difference between categorical variables. The level of significance, the p-value was 0.01 (p < 0.01). Results: The decision to choose between composite repair or replacement was influenced by whether this topic was taught to them at various undergraduate levels during Bachelor of Dental Surgery. The reason associated with the decision to repair defective composite restorations, 76% reported as cost-effective followed by Increased longevity (71%), the permanent filling (70%), patient’s preference for repair (65%), and least time consuming (50%). 67% participants preferred significantly (p